5‐aminosalicylate–intolerant patients are at increased risk of colectomy for ulcerative colitis. Issue 1 (7th November 2020) - Hibiya, Shuji; Matsuyama, Yusuke; Fujii, Toshimitsu; Maeyashiki, Chiaki; Saito, Eiko; Ito, Kimiko; Shimizu, Hiromichi; Kawamoto, Ami; Motobayashi, Maiko; Takenaka, Kento; Nagahori, Masakazu; Kurosaki, Masayuki; et al.
Summary: Background: Although 5‐aminosalicylate (5‐ASA) is the therapy of first choice in ulcerative colitis (UC), some patients cannot tolerate it because of side effects. Previous reports have not investigated whether 5‐ASA intolerance is associated with the risk of colectomy. Aim: To investigate the associations between 5‐ASA tolerance and colectomy among UC patients Methods: The data of UC patients who visited any of three hospitals during 2014‐2018 in and around Tokyo, Japan, were retrospectively obtained from the medical records. Patients were categorized as (a) tolerant to any 5‐ASA compounds ("tolerant to 5‐ASA") and (b) patients who were intolerant to one or more 5‐ASA compounds leading to refrainment from their further use ("intolerant to 5‐ASA"). The association between 5‐ASA tolerance and colectomy was examined by Cox proportional hazards model adjusted for sex, age, smoking and extent of colitis. Results: Of 1788 patients, 1684 were "tolerant to 5‐ASA" while 104 were "intolerant to 5‐ASA". Colectomy was performed in 43 (2.6%) of the patients tolerant to 5‐ASA and 12 (11.5%) of the patients intolerant to 5‐ASA. After adjusting for all covariates, the risk of undergoing colectomy was higher in the "intolerant to 5‐ASA" group than in the "tolerant to 5‐ASA" group (hazard ratio: 4.92; 95% confidence interval: 2.58‐9.38). Conclusion: Patients in whom 5‐ASA was discontinued due to intolerance had a higher risk of undergoing colectomy than patients tolerant to their first, second or third 5‐ASA compounds.